2016
DOI: 10.1038/srep29605
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of response to pegylated interferon in chronic hepatitis B: a real-world hospital-based analysis

Abstract: Information on the efficacy of pegylated interferon (PEG-IFN) treatment of chronic hepatitis B (CHB) patients and predictors of the response based on real-world data is limited. Consecutive 201 patients who underwent PEG-IFN treatment for CHB were reviewed. A virological response (VR) was defined as a serum HBV DNA of <2000 IU/mL, and a combined response (CR) was defined a VR accompanied by serological response for hepatitis B e antigen (HBeAg)-positive CHB. For HBeAg-positive CHB patients, the HBeAg seroconve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
31
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 37 publications
4
31
0
Order By: Relevance
“…Pretreatment HBsAg, viral load and ALT levels were highlighted to predict post-treatment response of IFN therapy. For CHB patients with pretreatment high ALT level, low viral load and low HBsAg level, treatment with IFN leads to better clinical outcomes [25][26][27][28]. Consistent with previous studies, in our study, we found that baseline ALT >4×ULN, HBV DNA <2×106 IU/mL and HBsAg <25000 IU/mL were significantly associated with EOT HBsAg ≤10 IU/mL.…”
Section: Discussionsupporting
confidence: 90%
“…Pretreatment HBsAg, viral load and ALT levels were highlighted to predict post-treatment response of IFN therapy. For CHB patients with pretreatment high ALT level, low viral load and low HBsAg level, treatment with IFN leads to better clinical outcomes [25][26][27][28]. Consistent with previous studies, in our study, we found that baseline ALT >4×ULN, HBV DNA <2×106 IU/mL and HBsAg <25000 IU/mL were significantly associated with EOT HBsAg ≤10 IU/mL.…”
Section: Discussionsupporting
confidence: 90%
“…Longer follow-up period Vitamin D Pathway SNPS and Response to Pegylated-Interferon in HBeAg-Negative Patients might have additional patients with HBsAg seroclearance. However, the number is similar to previous cohort studies (Brunetto et al, 2009;Moucari et al, 2009;Peng et al, 2012;Lampertico et al, 2013;Goulis et al, 2015;Wang et al, 2016). It is of interest that these SNPs might influent more on the long-term treatment outcome, in view of HBsAg seroclearance, a further study is required.…”
Section: Discussionsupporting
confidence: 71%
“…Several studies have demonstrated that certain baseline factors are associated with achieving HBeAg loss/seroconversion and a sustained off‐treatment HBV DNA response in patients receiving peg‐IFN‐α‐based regimens. These factors include HBV genotypes (genotypes A and B >C and D), higher baseline ALT levels (≥2 × ULN), lower HBV DNA levels (<2.0 × 10 8 IU/mL) and lower HBsAg levels (≤25 000 IU/mL) . In Study 149, the highest HBsAg loss rate (37.5%) at EOF was observed in genotype A patients receiving TDF plus peg‐IFN‐α for 48 weeks .…”
Section: Efficacy Of Peg‐ifnα−containing Regimens In Achieving a Funcmentioning
confidence: 94%
“…These factors include HBV genotypes (genotypes A and B >C and D), 5,27,32 higher baseline ALT levels (≥2 × ULN), 16,25,27,33 lower HBV DNA levels (<2.0 × 10 8 IU/ mL) 11,16,22,27,32 and lower HBsAg levels (≤25 000 IU/mL). 25,[32][33][34] In Study 149, the highest HBsAg loss rate (37.5%) at EOF was observed in genotype A patients receiving TDF plus peg-IFNα for 48 weeks. 13 A long-term, follow-up cohort study showed that baseline age and HBV genotype A were associated with the HBsAg loss rate at 5 years of off-treatment in HBeAg-positive patients treated with peg-IFNα plus ADV.…”
Section: Selection Of Treatment-naïve Patients Who Are More Likelymentioning
confidence: 97%